2010
DOI: 10.2214/ajr.09.2507
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Double Arterial Phase Hepatic MRI Using Adaptive 2D Centric View Ordering: Initial Clinical Experience

Abstract: High-resolution dual arterial phase 3D FSPGR MRI improves the timing of the arterial phase of liver enhancement and provides additional information for liver lesion detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Various studies have suggested that acquisition of multiple arterial phases can improve the detection of enhancement in liver lesions [14, 15]. Many groups perform dual arterial phase acquisition in one breath-hold to improve the conspicuity of arterial enhancement in small lesions [16]. However, the need to acquire data within a breath-hold requires a balance between temporal resolution, spatial resolution, and volumetric coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have suggested that acquisition of multiple arterial phases can improve the detection of enhancement in liver lesions [14, 15]. Many groups perform dual arterial phase acquisition in one breath-hold to improve the conspicuity of arterial enhancement in small lesions [16]. However, the need to acquire data within a breath-hold requires a balance between temporal resolution, spatial resolution, and volumetric coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Low et al found that younger patients required a shorter scan delay than older patients [9]. Kagawa et al showed a significant difference in the time of initial HCC enhancement between patients previously treated with transarterial chemoembolization and those who were treatment naïve [10].…”
Section: Discussionmentioning
confidence: 99%
“…Effective capture of the late arterial phase is essential for detection of small foci of hepatocellular carcinoma [5][6][7][8]; however, determining the precise timing of optimal contrast enhancement for detection of HCC is technically challenging because it is affected by the patient's cardiac output, choice of contrast agent, contrast injection protocol and imaging protocol [9,10]. More importantly, as with any dynamic MRI application, there is a tradeoff between spatial and temporal resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this faster imaging technique with multiple arterial phases allows using a fixed scan delay method to capture the transient arterial phase by making bolus timing less critical, while keeping the acquisition simple for the operator. Low et al (12) compared single arterial phase acquisition with dual arterial phase acquisition using a fixed 20‐s delay and reported 91% optimal timing with dual phase imaging, compared with 72% with single phase imaging. Similarly in our study, using a fixed scan delay of 10 s and Spiral LAVA with sliding window reconstruction at every 3‐s temporal update rate, optimal bolus timing was achieved in 88% of patients.…”
Section: Discussionmentioning
confidence: 99%